2015
DOI: 10.1111/1753-0407.12297
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of diabetes mellitus and prediabetes in the adult Romanian population: PREDATORR study

Abstract: The PREDATORR study shows a high prevalence of impaired glucose regulation in the adult Romanian population, providing data on the prevalence of DM and prediabetes and their association with several risk factors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
89
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 122 publications
(113 citation statements)
references
References 15 publications
3
89
1
1
Order By: Relevance
“…Yet, the first large scale national study on the prevalence of DM conducted in Romania recorded a different prevalence rate than the one included in the WHO latest Global Report on Diabetes [2]. Thus, in the PREDATORR study (PREvalence of DiAbeTes mellitus, prediabetes, overweight, Obesity, dyslipidemia, hyperuricemia and chronic kidney disease in Romania), the age-and sex-adjusted prevalence of DM was 11.6% (95% CI 9.6%-13.6%) [3]. PREDATORR study showed an increased prevalence of diabetes and prediabetes in Romania, almost double compared to the previous estimations [4].…”
mentioning
confidence: 99%
“…Yet, the first large scale national study on the prevalence of DM conducted in Romania recorded a different prevalence rate than the one included in the WHO latest Global Report on Diabetes [2]. Thus, in the PREDATORR study (PREvalence of DiAbeTes mellitus, prediabetes, overweight, Obesity, dyslipidemia, hyperuricemia and chronic kidney disease in Romania), the age-and sex-adjusted prevalence of DM was 11.6% (95% CI 9.6%-13.6%) [3]. PREDATORR study showed an increased prevalence of diabetes and prediabetes in Romania, almost double compared to the previous estimations [4].…”
mentioning
confidence: 99%
“…(19). More than 20 years ago, Allison et al, demonstrated that T2DM was more frequent in HCV liver cirrhosis compared with other etiologies (20).…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, Bartoş and Bădilă found a prevalence of 10.3% for diabetes [19]. The PREDATORR (PREvalence of DiAbeTes mellitus, prediabetes, overweight, Obesity, dyslipidemia, hyperuricemia and chronic kidney disease in Romania) study has shown an overall age-and sex-adjusted prevalence of diabetes in the general adult Romanian population of 11.6% (95%CI 9.6%-13.6%) [30]. In a study conducted in Slovakia, the prevalence of type 2 diabetes in Roma population was 30% versus 10% in the control population, obesity 65% (vs. 30% in controls) and metabolic syndrome 20% versus 4% in controls [22] .…”
Section: Discussionmentioning
confidence: 99%